Evaluating Birth Preparedness and Pregnancy Complications Readiness Knowledge and Skills of Accredited Social Health Activists in India - Smitha Kochukuttan, BDS, MPH; TK Sundari Ravindran, PhD; Suneeta Krishnan, PhD (Global Health and Education Projects, Inc., 2013)
Background: The National Rural Health Mission (NRHM) in India relies on Accredited Social Health Activists (ASHAs) to act as a link between pregnant women and health facilities. All ASHAs are required to have a birth preparedness plan and be aware of danger signs of complications to initiate appropriate and timely referral to obstetric care. Objectives: To examine the extent to which Accredited Social Health Activists (ASHAs) are equipped with necessary knowledge and skills and the adequacy of support they get from supervisors to carry out their assigned tasks in a rural district in Karnataka, (South) India. Methods: A cross-sectional descriptive study was carried out among 225 ASHAs between June -July 2011. Quantitative and qualitative data were collected using pre-tested semi-structured interview schedule. The data were analyzed using SPSS version 17. Chi-square test was used to determine associations between categorical variables. Results: The response rate was 207(92%). In terms of knowledge of all key danger signs (Complication Readiness), 2(1%), 10(4.8%), and 15(7.2%) ASHAs were aware of key danger signs for labor and child birth, postpartum period and pregnancy period, respectively. Knowledge of key danger signs was associated with repeated, recent and practical training (p <0.05). A majority (71%) scored 4-7 of the maximum score out of 8 for knowledge regarding Birth Preparedness. Conclusion and Public health implications: ASHAs in rural Karnataka, India, are poorly equipped to identify obstetric complications and to help expectant mothers prepare a birth preparedness plan. There is critical need for the implementation of appropriate training and follow-up supervision of ASHAs within a supportive, functioning and responsive health care system.